Analysis of the Experience of the State regulation of the Synthetic Fuel Sector in the Countries of the World - Kyzym Mykola O.; Shpilevskyi Volodymyr V.; Khaustov Mykyta M. (Problemi Ekonomiki)
The article examines the peculiarities of the State stimulation of the development of sectors for the production of synthetic liquid fuel from coal in the group of producing countries using CTL (Coal to Liquids) technologies. The article covers the historical period of formation and development of industrial production of synthetic liquid fuel from the 1930s to the present. It is determined that the industrial production of synthetic fuel in the world, in different historical periods, was localized in different countries and had different trends of formation and development that were determined by national regulatory policy. The main producers of synthetic liquid fuel in the studied period were the following countries: Germany from 1938 to 1945, the Republic of South Africa from 1945, China from 1947. It is revealed that the trigger for the development of synthetic fuel production in Germany and South Africa was the geopolitical situation, and in China the objective deficit of its own oil production. The driver of the development of synthetic liquid fuel in all countries was the State initiative implemented in the regulatory policy. Despite the fact that the goals of the regulatory policy in all the mentioned countries were similar, the approaches and means of implementation had a purely national specificity. The study of the essence and results of the implementation of the regulatory policy confirms its efficiency. Particular attention is paid to the experience of South Africa, where the production of synthetic liquid fuel went through the entire life cycle - from development to technological reconstruction. The experience of the People's Republic of China where the development of synthetic liquid production is integrated with the general economic development of the country is also interesting. The generalization and analysis of the world experience of the State regulation of the development of the septic liquid fuel sector made it possible to form the main directions of recommendations regarding the State stimulation of the development of the relevant industry sector in Ukraine.